2021
DOI: 10.1007/s10989-021-10333-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an Antimicrobial Peptide-Loaded Silk Fibroin/Gelatin Bilayer Sponge to Apply as a Wound Dressing; An In Vitro Study

Abstract: Recently, advanced biomaterial-based wound dressing due to bioactive properties have been considered and it has shown promising results. In this research, we prepared and improved an antibacterial silk fibroin/gelatin (SF/Gel) bilayer sponge scaffold loaded with various concentrations of a cationic antimicrobial peptide (CM11 peptide) as wound dressing for skin and soft tissue infections. The fabricated AMP-loaded SF/Gel sponge was completely designed and compared to the neat SF/Gel sponge in vitro. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The release of the CM 11 peptide after 500 min was observed from the samples, while the complete release of up to 80% was observed after 4000 min. The authors confirmed that compared to the blank (SF/Gel), the material modified with antimicrobial peptides demonstrated improved mechanical and antibacterial properties against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa [ 120 ].…”
Section: Biomedical Application Of Bilayer Hydrogelsmentioning
confidence: 88%
See 1 more Smart Citation
“…The release of the CM 11 peptide after 500 min was observed from the samples, while the complete release of up to 80% was observed after 4000 min. The authors confirmed that compared to the blank (SF/Gel), the material modified with antimicrobial peptides demonstrated improved mechanical and antibacterial properties against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa [ 120 ].…”
Section: Biomedical Application Of Bilayer Hydrogelsmentioning
confidence: 88%
“… ( a ) The swelling properties of the PVA-PAA and PVA samples in distilled water; and ( b ) the kinetics of swelling for the PVA-PAA samples at different pH values [ 120 ]. …”
Section: Figurementioning
confidence: 99%
“…The results showed that the fiber mats with peptides promoted wound healing in a shorter time than those without peptides. In a similar approach, a cationic antimicrobial peptide (CM11 peptide) was loaded into silk fibroin/gelatin bilayer sponges as wound dressing [ 300 ]. The sponges loaded with the peptide showed a controlled release without cytotoxicity on human foreskin fibroblasts (Hu02 ​cell line) and a significant antibacterial performance against Gram-positive and Gram-negative bacteria.…”
Section: Antimicrobial Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…Some studies, however, did not include biocompatibility assays [ 279 , 284 , 285 , 288 ]. Fibroblasts [ 293 , 294 , 299 , 300 , 302 , 304 ], fibroblast-like cells [ 301 ], epidermal [ 296 ], endothermal [ 297 ] and keratinocytes [ 298 , 303 ] were used as cell models to evaluate the cytotoxicity of antibacterial scaffolds prepared with antibacterial polymers, peptides and scaffolds incorporating carbon nanomaterials. The approaches reported by the in vivo assays also showed good wound healing efficacy [ 293 , 299 , 302 , 303 ].…”
Section: Toxicological Aspectsmentioning
confidence: 99%
“…To produce NPs, bacteria found in complex eukaryotic plants can be used to produce ionic nanoparticles (green synthesis). Because heat, pressure, and energy are not required, these bacteria can handle higher production levels [16][17][18][19][20]. A variety of adverse reactions can occur due to toxic chemicals adsorbing onto the surfaces of NPs.…”
Section: Introductionmentioning
confidence: 99%